Dissemination of the Independent Family Health Evaluation (IFHE) application in creating a healthy village in Tutul Village, Balung District - Diyan Indriyani; Asmuji Asmuji; Triawan Adi Cahyanto; Astrid Maharani; Sri Wahyuni A (Community Empowerment, 2021)
The empowerment of village community health is crucial to improve, one of which is by increasing family-based human resources. The ability to recognize the condition of the family's health status at an early stage can speed up the process of assisting health services based on the problems at hand, which can be accelerated with the Independent Family Health Evaluation (IFHE) application system. The dissemination of IFHE was carried out on August 9, 2021 in Tutul Healthy Village task force group, attended by 47 participants from the Community Association (RW) and Posyandu using the direct practice method. Later on, this group continued to disseminate information to the community through trial 1 and trial 2, each of which was held on 11-13 August 2021 for 400 families. From the dissemination program resulted that 319 families had no health risks, 64 families had a low risk, 10 families had a moderate risk and 7 families had a high risk. The IFHE application is very beneficial in quickly identifying the family health status. It is recommended that families routinely report their family's health status through the IFHE, so that the healthcare workers can use the information in making decisions to improve public health